1999
DOI: 10.5144/0256-4947.1999.547
|View full text |Cite
|
Sign up to set email alerts
|

Storing Insulin in a Clay Pot in the Desert Causes no Loss of Activity: A Preliminary Report

Abstract: The biological activity of insulin, like any protein, is affected if stored at extremes of temperature. The older, acidic form of insulin required refrigeration at 2 to 8°C, but the newer neutral formulation is much more stable at room temperature (15-30°C).1,2 Manufacturers recommend storing insulin under cool, shaded conditions, neither of which is available in the desert, where temperatures frequently exceed 40°C, thus constituting a major problem for diabetic patients. The possibility of adverse side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Insulin pump users should be taught to change the insulin in the reservoir more frequently, for example, on a daily basis, when the temperature is above 30°C. In areas where ambient temperatures may be as high as 45°C to 48°C, and where refrigeration is not available, insulin can safely be stored in local cooling devices with which temperatures of about 25°C to 26°C can be achieved . Poor glycemic control may be due to using insulin that has lost its potency, but this is often overlooked.…”
Section: Processes Of Carementioning
confidence: 99%
“…Insulin pump users should be taught to change the insulin in the reservoir more frequently, for example, on a daily basis, when the temperature is above 30°C. In areas where ambient temperatures may be as high as 45°C to 48°C, and where refrigeration is not available, insulin can safely be stored in local cooling devices with which temperatures of about 25°C to 26°C can be achieved . Poor glycemic control may be due to using insulin that has lost its potency, but this is often overlooked.…”
Section: Processes Of Carementioning
confidence: 99%
“…Easy access (24 h a day) for rapid diagnosis and initiation of treatment with availability of written protocols for management of diabetic ketoacidosis (DKA) and other presentations of childhood diabetes . Provision of practical care guidance at diagnosis includes the education required to enable the family to feel confident to provide diabetes care at home and have a basic understanding of the pathophysiology of diabetes and its treatment.…”
Section: Processes Of Carementioning
confidence: 99%
“…This requirement is a challenge for many thousands of families in low-and middle-income countries with hot climates, who do not have home refrigeration [10][11][12][13][14][15][16][17][18][19][20][21]. The International Diabetes Federation (IDF) Life for a Child (LFAC) Index study [21] reported that, in 30 of 37 low-and lower-middle income countries, at least 33% of families with children with diabetes did not have a home refrigerator.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes a solution is a neighbour's or local shop's refrigerator [10,11,13,17]. In many other cases in Africa, Asia and the Caribbean, insulin is stored in water-filled clay pots or other traditional storage devices, of various designs, using evaporative cooling [10][11][12][13][14][15][16][17][18][19][20]. Such clay pots ('zeer' pots, 'matka') are traditionally used in hot climates to keep water and foodstuffs cool [24,25].…”
Section: Introductionmentioning
confidence: 99%